Festa de Santo no Aguaçu : brincadeira de gente grande - Azevedo, Wagner Stephan de (2017)
The Festas de Santos is one of the essential features of the Cuiabana lowland. The District of Aguaçu, a reference context for this work, a rural area of the Capital of Mato Grosso, presents a network of cultural sociability of Festas de Santos, where a way of being, a way of life and a style of feeling of the people of the Cuiabana, which shares a festive Ethos local, where several traditional notions, traditional knowledge and practices of the inhabitants materialize, revealing a way of thinking that articulates through ritual practices (myths, narratives and rites): the social - the networks of sociability, horizontal plane of the feasts - and the cosmological one - the primordial foundation, the relation with the supernatural order, vertical plane -; And brings to light a kind of native knowledge which, although diffuse and porous, reveals that festivals are always an attempt to repeat the primordial, utopian and original foundation of the world, which is revitalized by means of promises and inheritances, gratitude and indebted debts of the gift, Which, having its root in the relation between the devotee and the Saint, imposes itself as the moving motor of the systems of festivals and causes in everyone the need to participate and belong to this festive world.